Gestión social y buen vivir en grupo de productores registrados de la empresa privada KAACAO S.A. en la ciudad de Chone - Bermeo Moreira, María Fernanda (2022)
The present titling work was carried out with the objective of evaluating the Social Management and Good Living of the registered producers of the private company KAACAO S.A., in order to determine their current status. The descriptive, bibliographic and field research consisted of three methodological phases required to fulfill the general objective: first, the current status of the registered producers was diagnosed through the development of evaluation instruments with indicators obtained from bibliographic review, and validation by the Delphi method, later an interview was applied to the general manager of the company, and a structured survey with a Likert scale to the 86 registered producers in Chone city, from this, the data obtained with the use SPSS software to measure reliability with Cronbach's Alpha and tabulate the results; in the second phase, the correlation between social management and good living was determined through the application of the Pearson test; in the third stage, an Ishikawa diagram was made to determine the problem and its causes. Finally, an improvement proposal was made using the 5W+2H matrix. The main results showed a satisfactory status on the indicators of the study variables, with the exception of the local environment, in addition to the lack of a business social management model. It is concluded that the social management of the company is correlated in high and positive values with the good living of the registered producers.